Organic cation transporter 3 on neuronal mitochondria mediates MPP+-induced mitochondrial dysfunction and neurotoxicity in a TIMM22-dependent manner - Ao Guan; Sida Han; Suzhen Liang; Weiwei Shen; Min Guo; Mei Cui (BMC Biology)
Abstract Background Mitochondria play crucial roles in cellular metabolism, and metabolite compartmentalization significantly impacts mitochondrial function and disease pathophysiology. MPP+ accumulation in mitochondria, a key factor in MPTP-induced neurodegeneration, leads to mitochondrial dysfunction, such as respiratory chain inhibition, ultimately leading to neuronal death. However, the mechanisms underlying mitochondrial MPP+ accumulation remain poorly understood. Organic cation transporter 3 (OCT3), a passive transporter mediating MPP+ transport, has been observed on the mitochondrial membrane, but it remains unclear whether mitochondrial OCT3 is involved in MPP+ accumulation in mitochondria. Results OCT3 was detected in the mitochondria fraction of SH-SY5Y cells, located on both the inner membrane and outer membrane. Following MPP+ incubation, there was a significant increase in mitochondrial uptake of MPP+, which was mitigated by OCT3 inhibition. Knockdown of the translocase of inner mitochondrial membrane 22 (TIMM22), an important component of the mitochondrial protein import apparatus, successfully reduced OCT3 levels on mitochondria without impairing mitochondrial morphology or mitochondrial membrane potential. TIMM22 knockdown reduced mitochondrial MPP+ uptake, which in turn rescued MPP+-induced mitochondrial fragmentation, complex I inhibition, and mitochondrial membrane potential reduction. Furthermore, TIMM22 knockdown suppressed caspase-9 and caspase-3 activation and reversed the alterations of BAX and BCL-xL induced by mitochondrial MPP+ accumulation. Conclusions Here we found that OCT3 on neuronal mitochondria serves as an effective MPP+ transporter, crucial for mitochondrial MPP+ uptake and MPP+-induced neurotoxicity. Furthermore, TIMM22 downregulation can selectively reduce mitochondrial OCT3 and reverse MPP+-induced mitochondrial dysfunction and neurotoxicity, highlighting TIMM22 and OCT3 as potential therapeutic targets for MPP+-associated neurodegeneration and diseases.